2014
DOI: 10.5586/am.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

Interactive physiological response of potato (Solanum tuberosum L.) plants to fungal colonization and Potato virus Y (PVY) infection

Abstract: Potato plants can be colonized by various viruses and by symbiotic, saprophytic and pathogenic fungi. However, the significance of interactions of viral infection and fungal colonization is hardly known. This work presents a model experiment in which the influence of three different types of fungal associations on the growth and physiology of the potato variety Pirol was tested individually or in combination with infection by PVY. It was hypothesized that simultaneous viral and fungal infections increase the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…ROS acting as long distance signal molecules play an important role during plant adaptation to biotic stress (Sewelam et al, 2016). Interestingly, our study revealed prolonged maintenance of elevated H 2 O 2 in mycorrhizal potato plantlets, which is in line with the previously described results (Thiem et al, 2014), however the basis of this observation is unclear and requires further consideration. Nevertheless, Hause and Fester (2005) demonstrated that H 2 O 2 is produced in arbuscules and the use of ROS scavengers (e.g., ascorbic acid and salicylhydroxamic acid) reduces both H 2 O 2 level and mycorrhizal development (Kapoor and Singh, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…ROS acting as long distance signal molecules play an important role during plant adaptation to biotic stress (Sewelam et al, 2016). Interestingly, our study revealed prolonged maintenance of elevated H 2 O 2 in mycorrhizal potato plantlets, which is in line with the previously described results (Thiem et al, 2014), however the basis of this observation is unclear and requires further consideration. Nevertheless, Hause and Fester (2005) demonstrated that H 2 O 2 is produced in arbuscules and the use of ROS scavengers (e.g., ascorbic acid and salicylhydroxamic acid) reduces both H 2 O 2 level and mycorrhizal development (Kapoor and Singh, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…We noticed that healthy plantlets colonized with R. irregularis displayed growth parameters similar to the control, with the only significant differences found in the higher root biomass (but not length) and higher chlorophyll content upon mycorrhization. Beneficial effect of AMF on root biomass production was already described for potato (Davies et al, 2005;Thiem et al, 2014) as well as for the other plant species (Saia et al, 2015;Chen M. et al, 2017;Jacott et al, 2017;Shao et al, 2018). We cannot exclude that enhanced biomass (but not the length) of root system could be associated with some structural changes that are known to be induced by AMF (e.g., enlargement of root cortex due to an extra cell layer development for accommodation of fungal structures) (Dreyer et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Significant attenuation of virus-induced plant disease following mycorrhizal establishment was shown in two research papers (Maffei et al., 2014; Thiem et al., 2014). Maffei et al.…”
Section: The Interactions Between Amf and Viruses In Potato And Othermentioning
confidence: 98%